Bioinformatics analysis of the complete nucleotide sequence of the Riemerella anatipestifer D15 gene - Feng, Bin; Cheng, Anchun; Wang, Mingshu (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
The bioinformatics analysis of D15 gene, encoding the 99-kDa major surface antigen D15 of Riemerella anatipestifer, the etiological agent of septicemia anserum exsudativa, was first provided in this article. The program DNAStar, ORF Finder, CDD, ClustalX, MEGA, NetNGlyc, NetOGlyc as well as NetPhos were performed to predict the characteristic of the D15 gene in physicochemical, construction of phylogenetic tree, N-glycosylation sites, O-glycosylation and phosphorylation sites of Riemerella anatipestifer. The D15 gene showed a conserved C-terminal region comprising the Bac_surface_Ag superfamily domain and a surface antigen variable number N-terminal region. This structure was similar to those of the analogous surface antigens of several gram-negative bacteria. To date, little information on the molecular characteristics of the R. anatipestifer D15 gene, and very few R. anatipestifer genomic sequences have been published, so all these consequences are valuable for further researches on more accurate molecular characteristics of R. anatipestifer D15.